PERANCANGAN ASET ILUSTRASI SEBAGAI ELEMEN VISUAL DIGITAL FEB DIGITAL AGENCY - Sifa Nur Faridi; Ine Rachmawati; Yuni Awalaturrohmah Solihah (Universitas Catur Insan Cendekia, 2026)
ABSTRACTThis design aims to address the problem of the lack and limitations of consistent internal illustration assets on FEB Digital Agency's social media, by designing flat design style illustration assets that are in line with the visual identity of FEB Digital Agency. The design process is carried out using the design thinking method which includes the stages of emphatize, define, ideate, prototype, and test. The results of this design are in the form of character illustration assets consisting of 4 teamwork activities and 4 content creator activities as well as 22 supporting element objects that can be used consistently. This design is expected to be able to increase visual appeal and strengthen the brand identity of FEB Digital Agency on social media. Keywords: Assets, Illustrations, Flat Design, Design Thinking